ANALISIS PENGARUH PRODUK, PELAYANAN, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI REVIEW KONSUMEN (Studi Kasus Pada Pengguna Platform Blibli.com) - Fitriani Siti Nurhodijah; Farida Indriani (Diponegoro Journal of Management, 2022)
In today's global era, especially in Indonesia, online buying and selling one commerce platforms has become a trend and societal necessity. Many e-commerce companies compete to dominate the existing market share, namely by developing a good marketing strategy to create a positive image in the minds of consumers. According to consumer media reports, Blibli.com is one of the Indonesian e commerce companies that is growing. However, Blibli.com frequently receives criticism from its customers regarding products, services, or promotions offered by Blibli.com. The purpose of this study is to examine the impact of products, services, and promotions on purchasing decisions, with consumer reviews serving as an intermediate variable on the object of the Blibli.com platform user. The number of samples used is 100, with respondents qualifying as users of the Blibli.com application who have made purchases and read shopping reviews on the Blibli.com application. The Structural Equation Model (SEM) analysis method is used in this study, with AMOS as a data processing tool. According to the findings of this study, products, promotions, and services, as well as consumer reviews, have a positive and significant impact on purchasing decisions.